Relationships of post-stroke fatigue with mobility, recovery, performance, and participation-related outcomes: a systematic review and meta-analysis - Usman, Jibrin S.; Wong, Thomson W. L.; Ng, Shamay S. M. (Frontiers in Neurology, 2024)
Background Effective post-stroke mobility, recovery, performance, and participation are key goals for stroke survivors. However, these outcomes may be hindered by post-stroke fatigue (PSF), which can affect numerous aspects of post-stroke mobility, recovery, performance, functioning, community participation, and return to work. This review aimed to assess the scientific evidence on the relationship between PSF and mobility function, functional recovery, functional performance, and participation-related outcomes among stroke survivors. Method A comprehensive search of Cochrane Central, PubMed, Embase, and Web of Science (WoS) databases was conducted from inception to December 2023. Observational, cross-sectional, and longitudinal studies were included. The methodological quality of the included studies was assessed using the National Institute of Health’s quality assessment tool, while the risk of bias was assessed using the Quality in Prognostic Studies tool. A total of 28 studies (n = 2,495 participants, 1,626 men, mean age ranging from 52.5 ± 9.5 to 71.1 ± 9.9 years) were included. The data analysis was conducted using narrative and quantitative synthesis. Fixed and random effects meta-analyses were conducted to explore the relationships between PSF and relevant outcomes. Results Chronic PSF was found to have significant negative correlations with mobility (meta r = −0.106, p < 0.001), balance performance (meta r = −0.172; 95%; p = 0.004), and quality of life (meta r = −0.647; p < 0.001). It also showed significant positive correlations with stroke impairment (meta r = 0.144, p < 0.001) and disability (meta r = 0.480, p < 0.001). Additionally, exertion/acute PSF had significantly negative correlations with walking economy (meta r = −0.627, p < 0.001) and walking endurance (meta r = −0.421, p = 0.022). The certainty of evidence was deemed moderate for these relationships. Conclusion Our findings indicate that higher levels of PSF are associated with poorer mobility, balance, and participation, as well as greater disability and stroke impairment. Future studies, especially prospective longitudinal and randomized controlled trials, are warranted to substantiate our findings. Systematic review registration PROSPERO, identifier: CRD42023492045.